THE EFFECT OF ADDITION OF CATFISH (Pangasius suchi) PROTEIN CONCENTRATE ON THE QUALITY OF SEAWEED FLAVORED NOODLE (Eucheuma cottonii) - Hardiwinata, Hardiwinata; Leksono, Tjipto; Sumarto, Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract The purpose of this study was to determine the effect of the addition of catfish(Pangasius suchi) protein concentrate (FPC) on the quality of seaweed flavored wet noodle. The method used in this research was the experimental method. The experiment was designedas completely randomized design (CRD) and the treatment was conducting by processing wet noodles, flavored with seaweed (Eucheuma cottonii)and addedwith the fishprotein concentrate at different amounts(0, 5, 10, 15 %). The results showed that the best quality of seaweed flavored noodle was produced by addition of 15% FPC. It was indicated by the highest value of appearance 6.7, aroma 7.4, taste 6.9 and texture 7.0.The proximate composition of the best product was showing the nutritional value contained the moisture of 43.37%, the protein of 55.81%, and the ash of 1.23. keywords:wet noodles, catfish, nutritional content